2021
DOI: 10.3389/fpsyg.2021.723035
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Factors and Depressive Symptoms Among Cardiac Nurses: A Cross-Sectional Study

Abstract: Background: The nursing profession is predisposed toward depressed mood and depressive symptoms. The multidirectionality and intensity of stressors in the nurses' occupational environment are of great significance in this respect. The study aimed to evaluate the impact of selected sociodemographic factors on depressive symptoms among cardiac nurses.Methods: This cross-sectional study included 336 cardiac nurses (302 women and 34 men) and was conducted between December 2019 and September 2020 in four hospital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
2
2
0
Order By: Relevance
“…Moreover, the adjusted model showed that those with a master degree had significantly fewer depressive symptoms than those with a diploma degree, which supports the results of Chi-square test analysis. This is similar to recent finding that cardiac nurses with lower academic qualification (bachelor versus master) had higher risk of depression [ 57 ]. The reason may be that the professionalism and psychological diathesis are more typically higher among nurses who receive more education [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the adjusted model showed that those with a master degree had significantly fewer depressive symptoms than those with a diploma degree, which supports the results of Chi-square test analysis. This is similar to recent finding that cardiac nurses with lower academic qualification (bachelor versus master) had higher risk of depression [ 57 ]. The reason may be that the professionalism and psychological diathesis are more typically higher among nurses who receive more education [ 58 ].…”
Section: Discussionsupporting
confidence: 91%
“…Comparing our results regarding mental health to other research carried out among nurses in Poland, the burnout scores in our sample are comparable to the ones found in research by Ogińska-Bulik 46 and the insomnia symptoms were higher than in a study by Andrzejewska et al 47 Depression scores were much higher than in a study by Larysz and Uchmanowicz, 48 even though their study overlapped the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 86%
“…Those findings suggest a potential marital trade‐off for women, in which spousal support may decrease genetic effects of perceived stress on depressive symptoms, although marital and family demands may increase environmental effects on depressive symptoms. Likewise, Larysz and Uchmanowicz reported that the prevalence of depressive symptoms among cardiac nurses is affected by marital status; those in a relationship had lower PHQ‐9 scores (less depression) compared to being single or widowed 24 . A strong social support network may be important considerations in the treatment of persons with VWD.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Larysz and Uchmanowicz reported that the prevalence of depressive symptoms among cardiac nurses is affected by marital status; those in a relationship had lower PHQ-9 scores (less depression) compared to being single or widowed. 24 A strong social support network may be important considerations in the treatment of persons with VWD.…”
Section: Discussionmentioning
confidence: 99%